On-tissue phospholipase C digestion for enhanced MALDI-MS imaging of neutral glycosphingolipids - Vens-Cappell, Simeon; Porubský, Štefan (Analytical chemistry, 2016)
Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) can be used to simultaneously visualize the lateral distribution of different lipid classes in tissue sections, but the applicability of the method to real-life samples is often limited by ion suppression effects. In particular, the presence of abundant phosphatidylcholines (PCs) can reduce the ion yields for all other lipid species in positive ion mode measurements. Here, we used on-tissue treatment with buffer-free phospholipase C (PLC) to near-quantitatively degrade PCs in fresh-frozen tissue sections. The ion signal intensities of mono-, di-, and oligohexosylceramides were enhanced by up to 10-fold. In addition, visualization of Shiga toxin receptor globotriaosylceramide (Gb3Cer) in the kidneys of wild-type and α-galactosidase A-knockout (Fabry) mice was possible at about ten micrometer resolution. Importantly, the PLC treatment did not decrease the high lateral resolution of the MS imaging analysis.
Gesehen am 28.06.2019